Cell phone intervention for you (CITY): A randomized, controlled trial of behavioral weight loss intervention for young adults using mobile technology. (November 2015) - Svetkey, Laura P.; Batch, Bryan C.; Lin, Pao-Hwa; Intille, Stephen S.; Corsino, Leonor; Tyson, Crystal C.; Bosworth, Hayden B.; Grambow, Steven C.; Voils, Corrine; Loria, Catherine; Gallis, John A.; Schwager, Jenifer; et al.
Abstract : Objective: To determine the effect on weight of two mobile technology‐based (mHealth) behavioral weight loss interventions in young adults. Methods: Randomized, controlled comparative effectiveness trial in 18‐ to 35‐year‐olds with BMI ≥ 25 kg/m 2 (overweight/obese), with participants randomized to 24 months of mHealth intervention delivered by interactive smartphone application on a cell phone (CP); personal coaching enhanced by smartphone self‐monitoring (PC); or Control. Results: The 365 randomized participants had mean baseline BMI of 35 kg/m 2 . Final weight was measured in 86% of participants. CP was not superior to Control at any measurement point. PC participants lost significantly more weight than Controls at 6 months (net effect −1.92 kg [CI −3.17, −0.67], P  = 0.003), but not at 12 and 24 months. Conclusions: Despite high intervention engagement and study retention, the inclusion of behavioral principles and tools in both interventions, and weight loss in all treatment groups, CP did not lead to weight loss, and PC did not lead to sustained weight loss relative to Control. Although mHealth solutions offer broad dissemination and scalability, the CITY results sound a cautionary note concerning intervention delivery by mobile applications. Effective intervention may require the efficiency of mobile technology, the social support and human interaction of personal coaching, and an adaptive approach to intervention design.